ON, TO, AT, IN RISK ANALYSIS BASED ON ISO 31000 TO IMPROVE OPERATIONAL EFFECTIVENESS AT RAKHA LAUNDRY IN GOWA REGENCY: ANALISIS RISIKO BERBASIS ISO 31000 DALAM MENINGKATKAN EFEKTIFITAS OPERASIONAL PADA USAHA RAKHA LAUNDRY DI KABUPATEN GOWA - Asmayanti, Asmayanti; Syam, Agus; Sudarmi, Sudarmi; Haruna, Hasisa; Nurhikmah, Andi Reski (Universitas Ichsan Sidenreng Rappang, 2025)
This research aims to analyze and mitigate risks to improve operational effectiveness at Rakha Laundry in Pattallassang, Gowa Regency. This business has been operating for a year but has encountered operational challenges that lead to waste, machine breakdowns, service delays, and even customer losses. These issues must be addressed to maintain business stability and sustainability. The research method used was a qualitative approach, utilizing primary and secondary data through observation and interviews. The risk mitigation tool used was ISO 31000. The results of the study show that risks and their mitigation are grouped into three levels, namely High, Medium, and Low. High Level Risk (1) Limited Human Resources; Education and Training, (2) Machine Damage; routine maintenance and supervision. (3) Lost/Exchanged clothes; SOP, CCTV, and employee training. Medium Level Risk (1) Power outages; procurement of generators or communicating to customers. (2) Floods; Prepare security, control receipts, and predict flooding based on the volume and duration of rain. (3) Poor quality, ironing is not neat, not clean, faded or damaged clothes; SOP, supervisor, reward and punishment. Low Level Risk (1) Employees are late; absenteeism, salary deductions and bonuses for disciplined employees. (2) Fluctuating material prices; Purchase materials from suppliers and determine prices by considering fluctuations. (3) Competitors; Improve skills through learning, training, and mentoring. Keywords: Risk Analysis, Effectiveness, ISO 31000.